The effect of reaction time and oil-to-methanol ratio on the calorific value of biodiesel produced from chicken fat oil - Habib, Alltop Amri Ya; Emrinaldi, Tengku; Yolanda, Yogi; Azis, Yelmida (Universitas Riau, 2025)
The energy content of a fuel is represented by its calorific value. When biodiesel combusts in the presence of air or oxygen, the heat released during the combustion process is expressed as the calorific value. This study aims to analyze the effect of reaction time (60, 120, and 180 minutes) and the volume ratio of chicken fat oil-to-methanol (OM) (25:30 and 25:50) in the transesterification process on the calorific value of the produced biodiesel. The transesterification process was conducted using MgO as a catalyst under various reaction times and OM ratios. The produced biodiesel was then analyzed to determine its calorific value as a key fuel quality parameter. The results indicate that a longer reaction time and a higher OM volume ratio lead to an increase in the calorific value. The highest calorific value obtained in this study was 9952 kcal/kg, achieved at a reaction time of 180 minutes and an OM volume ratio of 25:50.